Bowel habit, diet and body weight in preadolescent children - Jennings, A; Davies, G.J; Costarelli, V; Dettmar, P.W (Journal of human nutrition and dietetics, 2010)
The possible influence of diet and body weight on bowel habit in children is unknown. The present study aimed to investigate the inter-relationships between bowel function, excess body weight and dietary intake in a group of preadolescent children. Eighty-four preadolescent children aged 7-10 years were recruited [mean (SD) age 9.7 (1.0) years]. All children completed a bowel habit diary, examining specific parameters of bowel function and a weighed food inventory concurrently for seven consecutive days. Height and weight measurements were also taken. Children were grouped according to whether they met dietary recommendations and by overweight status; differences in bowel function between the groups were then analysed. Children who exceeded reference values for fat were more likely to report an incidence of straining to start (P = 0.005) and pain during defaecation (P = 0.021). Subjects who met protein recommendations were less likely to report incomplete evacuation (P = 0.000) and those who met zinc recommendations were less likely to report pain during defaecation (P = 0.044). Excess body weight (according to International Obesity Task Force cut-offs) was also associated with poor bowel habit, with overweight and obese children reporting lower defaecation frequency and a higher incidence of straining and feelings of incomplete evacuation, although these findings were not statistically significant. Defaecation frequency in healthy children was 1.4 defaecations per day compared to 1.2 defaecations for overweight and obese children. A poor diet that fails to meet dietary recommendations as well as being overweight and obese appears to be associated with increased defaecation problems in preadolescent children.